2020
DOI: 10.3348/kjr.2020.0112
|View full text |Cite
|
Sign up to set email alerts
|

2019 Novel Coronavirus (COVID-19) Pneumonia: Serial Computed Tomography Findings

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new virus recently isolated from humans. SARS-CoV-2 was discovered to be the pathogen responsible for a cluster of pneumonia associated with severe respiratory disease occurred in December 2019 in China. This novel pulmonary infection, formally called coronavirus disease 2019 (COVID-19), has spread rapidly in China and beyond. On 8 March 2020, the number of Italians with SARS-CoV-2 infection was 7375 with a 48% hospitalization rate. At present, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 9 publications
4
82
0
5
Order By: Relevance
“…Computed tomography (CT) imaging is considered the most effective method for the detection of lung abnormalities, particularly in the early stage of the disease [4,[6][7][8][9][10][11][12]. Moreover, serial chest CT imaging with different time intervals (from three to seven days) is also effective in assessing the disease progression (from the time of initial diagnosis of COVID-19 until patient discharge) [6,7,13].…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) imaging is considered the most effective method for the detection of lung abnormalities, particularly in the early stage of the disease [4,[6][7][8][9][10][11][12]. Moreover, serial chest CT imaging with different time intervals (from three to seven days) is also effective in assessing the disease progression (from the time of initial diagnosis of COVID-19 until patient discharge) [6,7,13].…”
Section: Introductionmentioning
confidence: 99%
“…Thin-section chest CT scans have been contributing greatly to the disease assessment and patient condition surveillance in relation to . Researchers in radiology have reported that typical imaging features of COVID-19 patients include ground-glass opacity (GGO) (6,7), crazy-paving pattern, and consolidation (8). Once discharged, a sizable amount of patients had almost no CT abnormalities (9); yet many still demonstrated apparent residual parenchymal abnormalities on follow-up chest CT scans (10).…”
mentioning
confidence: 99%
“…It is important to highlight that 134 the CT scan can be normal during initial days, and a normal CT scan in a suspected case would 135 never definitely rule out the diagnosis of COVID-19 [18]. Moreover, the CT scan is dynamic in 136 patients with COVID-19 and changes rapidly [19][20][21]. The earliest abnormal finding in the CT 137 scan is the appearance of ground-glass opacities in peripheral and sub-pleural areas [22].…”
Section: Discussion: 95mentioning
confidence: 99%
“…Lastly, 180 there are different therapeutic strategies for COVID-19 patients, but we don't have enough data 181 for their efficacy. Additional investigations including randomized controlled trials will be 182 necessary to further our understanding in the treatment of COVID- 19…”
Section: Discussion: 95mentioning
confidence: 99%